Cubic formulas for computing the zeros of certain quaternionic polynomial. (25th January 2017) - Liu, Ming‐Sheng; Tang, Yan
Abstract : In this paper, we derive the explicit formulas for computing the zeros of certain cubic quaternionic polynomial. From these, we obtain a necessary and sufficient condition to quaternionic cubic polynomial have a spherical zero, and some examples are also provided. Moreover, we will discuss some applications of the cubic quaternionic formulas. Copyright © 2017 John Wiley & Sons, Ltd.